ANALISIS HIGHER ORDER THINKING SKILLS (HOTS) SISWA MAN 2 MODEL PEKANBARU DALAM MENYELESAIKAN SOAL UJIAN NASIONAL FISIKA TINGKAT SMA/MA - ', Elyana; ', Yennita; ', Fakhruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: This study aims to determine the percentage of the national exam physics category Higher Order Thinking Skills (HOTS) and know the high-level thinking skills of students in completing the national exam Physics. The method used in this research is descriptive with the type of content or document analysis. The subject of this research is a class XII student with the number 129. The data obtained in this study a matter of Physics 2016 percentage categorized HOTS are analyzed using indicators about by A. Thomas and G. Thorne as well as data analysis of high-level thinking skills of students in the national exam physics obtained through answer students' work on the problems. Based on data analysis can be concluded that the national exam physics is capable of measuring high-level thinking skills of students on average are less well categorized.Key Words: Higher Order Thinking Skills, HOTS Students, National Physical Exam